Association of epidural analgesia during labor with neurodevelopment of children during the first three years: the Japan Environment and Children's Study - Masayuki Shima; Narumi Tokuda; Hideki Hasunuma; Yoshiko Kobayashi; Hiroyuki Tanaka; Hideaki Sawai; Hiroaki Shibahara; Yasuhiro Takeshima; Munetaka Hirose; the Japan Environment and Children's Study (JECS) (Komiyama Printing Co. Ltd, 2022)
Background: Epidural analgesia relives pain during labor. However, the long-term effects on neurodevelopment in children remain unclear. We explored associations between exposure to epidural analgesia during labor and childhood neurodevelopment during the first 3 years of life, in the Japan Environment and Children's Study (JECS), a large-scale birth cohort study. Methods: Pregnant women were recruited between January 2011 and March 2014, and 100,304 live births of singleton children born at full-term by vaginal delivery, and without congenital diseases were analyzed. Data on mothers and children were collected using a self-administered questionnaires and medical record transcripts. The children's neurodevelopment was repeatedly assessed for five domains (communication, gross motor, fine motor, problem solving, and personal-social), using the Ages and Stages Questionnaires, Third Edition, at six time points from age 6 to 36 months. After adjusting for potential confounders, the associations between exposure to epidural analgesia during labor and children's neurodevelopment at each time point were assessed. Results: Of the 42,172 children with valid data at all six time points, 938 (2.4%) were born to mothers who received epidural analgesia during labor. Maternal exposure to epidural analgesia was associated with neurodevelopmental delays during the first 3 years after birth. Delay risks in gross and fine motor domains were the greatest at 18 months (adjusted odds ratio (aOR) [95% confidence interval (CI)]: 1.40 [1.06, 1.84] and 1.54 [1.17, 2.03], respectively), subsequently decreasing. Delay risks in communication and problem-solving domains were significantly high at 6 and 24 months, and remained significant at 36 months (aOR [95% CI]: 1.40 [1.04, 1.90] and 1.28 [1.01, 1.61], respectively). Exposure to epidural analgesia was also associated with the incidence of problem solving and personal-social delays from 18 to 24 months old. Neurodevelopmental delay risks, except for communication, were dominant in children born to mothers aged ≥30 years at delivery. Conclusions: This study showed that maternal exposure to epidural analgesia during labor was associated with neurodevelopmental delays in children during the first 3 years after birth.